FRI0345 Neurological Manifestations of Primary Sjögren Syndrome. (15th July 2016) - Fernandez Castro, M.; Andreu, J.L.; Sanchez-Piedra, C.; Rosas, J.; Martinez Taboada, V.; Olive, A.
Abstract : Background: Primary Sjögren syndrome (pSS) is a chronic systemic autoimmune disease with a relevant impact in patients' quality of life. Neurological manifestations of pSS could have an important impact on morbidity and mortality. Objectives: The aim of our study was to evaluate central and peripheral neurological manifestations of a pSS cohort of patients assisted in Spanish Reumathology Departments. Methods: This is a multicentre descriptive transversal study of pSS patients from thirty-three rheumatology departments. Patients fulfilling European/American consensus criteria were included after randomisation. By reviewing clinical records and interviewing the patients, we collected epidemiological, clinical, serologic, therapeutic, and disease activity indexes data. Informed consent was obtained and local ethics committees approved the study. Variables were analysed by descriptive statistical methods, using means, medians, and rates. Chi-square was used to establish the statistical associations, being considered a p<0.05 as significant. Results: Four hundred and thirty-seven patients were included. Ninety five percent of them were women. The median age of the cohort was 58 years. Thirty-four (7.8%) patients developed central nervous system (CNS) involvement. Interestingly, 15 patients developed CNS manifestations before the diagnosis of pSS. Fourteen patients referred headache, 11 patients some psychiatric disorder, 6 patients cerebral ischemic attack, 5 patients cognitive impairment, 5 patients multiple sclerosis, 3 patients cranial nerve involvement of central origin, 3 patients cerebral vasculitis, 2 patients optic neuritis, a patient aseptic meningitis and a patient myelopathy. ESSDAI index was significantly higher in patients with CNS involvement. Systemic treatments (glucocorticoids, bolus of glucocorticoids, azathioprine, methotrexate and cyclophosphamide) and biological treatments (anti-TNF, abatacept and tocilizumab) were used significantly more frequently in patients with CNS impairment. Thirty-nine (8.9%) patients developed peripheral nervous system (PNS) involvement, 14 of them, before the diagnosis of pSS. Thirteen patients had mixed polyneuropathy, 2 patients motor polyneuropathy, 8 patients sensitive polyneuropathy, 3 patients small fiber neuropathy, a patient developed mononeuritis multiplex and 8 patients focal mononeuropathy. Three patients had trigeminal sensory neuropathy, a patient III cranial neuropathy and 3 patients VII cranial neuropathy. SSDAI and ESSDAI indexes were significantly higher in patients with PNS involvement. Systemic therapies (glucocorticoids, bolus of glucocorticoids, methotrexate, mycophenolate mofetil and cyclophosphamide), biological treatments (rituximab) and intravenous immunoglobulins were used significantly more frequently in patients with PNS impairment. Conclusions: More than 7% of pSS patients with pSS of our cohort developed nervous system manifestations. The CNS and PNS involvement led to a significantly higher disease activity, scored by formal activity indexes. The use of systemic and biological treatment was significantly higher in patients with nervous system involvement. Disclosure of Interest: None declared